Exploring the influence of task and environmental constraints on batting and bowling performance in cricket: A systematic review - Singh, U.; Ramachandran, A. K.; Doma, K.; Connor, J. D. (International Journal of Sports Science & Coaching, 2023)
Cricket is an unique international sport where environmental and task constraints have shown to have a significant impact on batting and bowling performance. The aim of this systematic review was to determine the effect of task and environmental constraints on cricket performance. A systematic literature search was conducted across Scopus, PubMed, Web of Science, CINAHL, and SportDiscus. Studies were deemed eligible if they reported the effects of pitch type, pitch length, equipment (e.g. cricket bat, batting pads, ball type, etc.) on cricket performance. A total of 20 studies met the inclusion criteria with Kmet score ranging between 75% and 92%. The results from this study demonstrate that environmental constraints such as pitch-type and task constraints such as equipment modification (e.g. type of cricket bat, batting pads, ball) and pitch length can influence cricketer's batting and bowling performance. Scaling cricket bats and reducing pitch length were acutely beneficial to cricket batting, while ball type, pitch length and soil properties were impactful on bowling performance. Importantly though, the impact of constraint manipulation seemed to be influenced by the skill level of the performer. The findings from this study may help to inform coaches and practitioners improve skill acquisition, through constraint manipulation, to develop highly adaptive cricket batting and bowling skill.